South-South urban infrastructure research. Why is it important? Reflections on the ‘best-practice’ phenomenon - Odendaal, Nancy (AESOP, 2016)
Colombia cities have become well known for their innovative approaches to public transportation, and specifically around the relationship between transport and land use. The fact that these cities are located in the global South has captivated the imaginations of South African city policy makers as the potentials for south-south transfer of learning and knowledge are touted. My sabbatical journey to Latin America was, to a large extent, informed by the prospect for such collaboration as well as an ethical position that insists on foregrounding the South in urban studies. In this presentation I reflect on my sabbatical work in anticipation of future comparative urban research on Colombia and South Africa. Throughout my stay a nagging question was, in learning from cities like Bogota and Medellin, do we learn what we need to learn? What I mean is, are the socio-technical relations generated (and in some ways assumed) by infrastructure investments such as Transmilenio in Bogotá and the Metro-cables in Medellin receiving adequate attention in comparative research work as well as policy adoption? Both these initiatives are embedded in political, geopolitical and temporal contexts that concern so much more than infrastructure investment – they have had profound socio-political implications that go beyond their material impacts. It is tempting to be carried away by the material angles of these investments – and I would hypothesize that their application in the South Africa context has been largely infrastructure-driven. What is needed, is an approach to research that uncovers the socio-technical relations that informs these interventions in order to learn what we need to learn; how the material can generate broader social change.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south